Conversations with Australian Indigenous Females Revealing Their Motives When Establishing a Sustainable Small Business - L., Cecil A. (Information Management and Business Review, 2012)
The Australian government has expressed commitment for Aboriginal entrepreneurship contending it is a pathway for ameliorating poverty, improving economic self-reliance, and building life quality. Yet a restrained geographic and sector spread of Australian Indigenous small business suggests there may be other important motives for starting an enterprise. This paper narrates responses from conversations with Aboriginal women ata remote settlement in the Northern Territory of Australia to reveal they were driven not by desires to acquire wealth, improve their educational opportunities or to escape poverty, but by practical aspirations of operating a local store selling household commodities used in daily living, a coffee shop meeting place, and to meaningfully change their existing community roles enabling them to ‘get off welfare’. Documenting the experiences and expectations of these Indigenous women exposes how Aboriginal culture, family, and community socialising networks can contribute to fostering female entrepreneurship.